2011
DOI: 10.1016/j.cell.2011.05.024
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Clonal Analysis Reveals Self-Renewing and Multipotent Adult Neural Stem Cell Characteristics

Abstract: Summary Neurogenesis and gliogenesis continue in discrete regions of the adult mammalian brain. A fundamental question remains whether cell genesis occurs from distinct lineage-restricted progenitors or from self-renewing and multipotent neural stem cells in the adult brain. Here, we developed a genetic marking strategy for lineage-tracing of individual, quiescent, and nestin-expressing radial glia-like (RGL) precursors in the adult mouse dentate gyrus. Clonal analysis identified multiple modes of RGL activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

40
941
7
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 767 publications
(990 citation statements)
references
References 54 publications
40
941
7
2
Order By: Relevance
“…We did not observe increases in Hes5CreER T2 -derived polymorphic astrocytes (S100β + ) over time, confirming results from clonal analysis of SGZ NSCs 11 . We also did not observe Hes5 + NSC-derived oligodendrocytes; hence, in accordance with other reports, adult DG NSCs are mainly neurogenic and do not contribute majorly to gliogenesis in vivo 6,11,14,17,47,49 .…”
Section: Hes5creersupporting
confidence: 92%
“…We did not observe increases in Hes5CreER T2 -derived polymorphic astrocytes (S100β + ) over time, confirming results from clonal analysis of SGZ NSCs 11 . We also did not observe Hes5 + NSC-derived oligodendrocytes; hence, in accordance with other reports, adult DG NSCs are mainly neurogenic and do not contribute majorly to gliogenesis in vivo 6,11,14,17,47,49 .…”
Section: Hes5creersupporting
confidence: 92%
“…Embryonic cortical stem cells have smooth spheroid cell bodies that extend long smooth processes, which enable newly formed neurons to migrate into the cortical plate (30). In the adult dentate gyrus, however, the observation of individual clones suggest that adult-born neurons do not migrate alongside the radial process of their mother cells, but instead migrate tangentially away from it, before integrating into the GCL (24,31). We therefore believe that the reasons for their complex radial morphologies lie in the regulatory mechanisms of the neurogenic niche.…”
mentioning
confidence: 99%
“…RGL neural stem cells of the adult dentate gyrus also express astrocytic markers, but comprise a heterogeneous population based on the molecular markers they express, the morphologies they exhibit (17)(18)(19)(20)(21)(22), and their fate (23)(24)(25)(26)(27)(28). Nestin-GFP-positive RGL stem cells account for more than 70% of RGL stem cells in the SGZ of the dentate gyrus (24), but it was recently found that not all Nestin-GFP-positive cells with RGL morphology have stem cell properties (29): type β cells, which arborize in the granule cell layer (GCL) but do not reach the molecular layer (ML) of the dentate gyrus, account for 26% of Nestin-GFP-positive RGL stem cells. They express stem cell (Sox1, Sox2, Prominin 1, GFAP, and Nestin) and astrocytic [GFAP, glial glutamate tranporter 1 (GLT1), and S100β] markers but do not proliferate.…”
mentioning
confidence: 99%
“…Under basal conditions, neural stem cells can either be in a resting, quiescent state, or they can be actively dividing [23,28,29]. Proliferating stem cells are capable of continuous self-renewal through mitotic cell division, and can differentiate into a number of different cell types, such as neurons, astrocytes and oligodendrocytes.…”
Section: Adult Hippocampal Neurogenesismentioning
confidence: 99%